Anatomical study on origin, course and distribution of cranial and caudal mesenteric arteries in the White New Zealand rabbit (Orycotolagus cuniculus) - Uddin, M; Rahman, ML; Alam, MA; Ahasan, ASML (International Journal of Natural Sciences, 2012)
The present study was carried out on fifteen healthy adult White New Zealand rabbit (Orycotolagus cuniculus) to clarify the obscure mesenteric arteries, which and their branches which are usually involved in intestinal surgery. The mesenteric artery is a high caliber vessel, 2cm in length dependent on the abdominal aorta, right below the emergence of the vessels destined for the liver and stomach. The animals were sacrificed, injecting diazepam (30 mg/kg) in jugular vein. Cannulation of the abdominal aorta, perfusion with warmed water (40ºC) and stained latex injection (Neoprene 450, Capitol Scientific, Austin, U.S.A, Red carmine stain) were performed, followed by fixation. With formalin (10%) the dissection and photographic documents (Casio Cyber-shot, 12.1 mega pixels) made it possible to systemize the arteries and define the vascular patterns of the viscera. The results prone that the cranial mesenteric artery of the White New Zealand rabbit (Orycotolagus cuniculus) arose from the abdominal aorta, at the level of the second lumbar vertebra, entered the cranial mesentery forming its root, then proceeded caudoventrally in the mesojejunum and continued as the last cecal artery. The cranial mesenteric artery gave off: - Caudal pancreaticoduodenal artery to the right lobe of the pancreas and the descending and ascending parts of the duodenum. Middle colic artery, a small vessel (frequently two) arising from the left wall and passing to the transverse colon, Eighteen to twenty jejunal arteries, Ileocecocolic artery to the ileum, cecum, ascending colon, transverse colon and the cranial part of the descending colon. The caudal mesenteric artery arose from the abdominal aorta at the level of the caudal border of the root of the 6th lumbar transverse process, passed caudoventrally in the descending mesocolon, then divided into: left colic artery to the caudal two thirds of the descending colon, and cranial rectal artery to the cranial segment of the rectum. The obtained results were compared with their corresponding in the domestic animals, especially the domestic carnivores and laboratory animals. DOI: http://dx.doi.org/10.3329/ijns.v2i2.11386 International Journal of Natural Sciences (2012), 2(2):54-59